2020
DOI: 10.1105/tpc.20.00598
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of LACCASE8 Facilitates Polymerization of Caffeyl Alcohol for C-Lignin Biosynthesis in the Seed Coat of Cleome hassleriana

Abstract: LACCASE8 from the model system Cleome hassleriana possesses the unusual property of oxidizing caffeyl alcohol but not coniferyl alcohol and plays a critical role in initiating C-lignin polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 80 publications
2
55
0
Order By: Relevance
“…Together with previous findings (Hiraide et al, 2014, 2016), our current data demonstrated that precise localisation of a laccase, CoLac1, with a prominent PA‐polymerisation ability facilitates the S 2 L‐specific deposition of H‐type lignin units during compression wood formation in the coniferous gymnosperm C. obtusa . Similarly, it was recently shown that, in the seed coat of Cleome hassleriana , the seed‐coat‐specific deposition of atypical catechol (C)‐type lignin polymers (catechyl lignin) is mediated by a laccase, ChLac8, which shows a preferential oxidation ability towards C‐type lignin monomer (caffeyl alcohol) (Wang et al, 2020). Collectively, these findings provide evidence that not only the spatial localisation of laccases, but also their biochemical characteristics, impact the spatial patterning of lignin polymerisation in planta .…”
Section: Discussionmentioning
confidence: 99%
“…Together with previous findings (Hiraide et al, 2014, 2016), our current data demonstrated that precise localisation of a laccase, CoLac1, with a prominent PA‐polymerisation ability facilitates the S 2 L‐specific deposition of H‐type lignin units during compression wood formation in the coniferous gymnosperm C. obtusa . Similarly, it was recently shown that, in the seed coat of Cleome hassleriana , the seed‐coat‐specific deposition of atypical catechol (C)‐type lignin polymers (catechyl lignin) is mediated by a laccase, ChLac8, which shows a preferential oxidation ability towards C‐type lignin monomer (caffeyl alcohol) (Wang et al, 2020). Collectively, these findings provide evidence that not only the spatial localisation of laccases, but also their biochemical characteristics, impact the spatial patterning of lignin polymerisation in planta .…”
Section: Discussionmentioning
confidence: 99%
“…In C. hassleriana , accumulation of ChLAC8 parallels that of C‐lignin during seed coat development, and ChLAC8 polymerizes caffeyl alcohol instead of coniferyl alcohol to generate dimers or trimers of caffeyl alcohol in vitro . The accumulation of C‐lignin in the seed coats of transgenic Cleome plants is clearly repressed as a result of inhibition of ChLAC8 expression, implying that ChLAC8 is required for the polymerization of C‐lignin in C. hassleriana (Wang et al, 2020g). In A. thaliana , the lac4 lac11 lac17 triple mutant exhibits a lack of lignification in the vascular and dampened plant growth, whereas lignification of the Casparian strip, which is catalyzed by peroxidase, is not disrupted.…”
Section: Biosynthesis Of Phenylpropanoid Metabolitesmentioning
confidence: 99%
“…To address this open question, we generated a comprehensive phylogeny of all LACs from 10 taxonomically diverse species with published reference genomes (Figure 5). In contrast to previous phylogenies (McCaig et al, 2005;Turlapati et al, 2011;Zhao et al, 2013;Wang X. et al, 2020;Yonekura-Sakakibara et al, 2020), we used only full-length sequences (to avoid partial homology due to incomplete sequences) and included ascorbate oxidases as an outgroup to distinguish between the two families of multicopper oxidases. We moreover chose a bayesian FIGURE 5 | Phylogenetic analysis of LAC homologs.…”
Section: Laccases Distribution Of Laccases Among Kingdoms and Speciesmentioning
confidence: 99%